Single stage substernal thyroidectomy and off-pump coronary artery bypass grafting: Is it worth using cardiopulmonary bypass unless absolutely necessary? - Çetin, Erdem; Özyüksel, Arda; Dalbaşı, Erkan (BMJ Publishing Group, 2014)
It is a rare entity to observe the coexistence of thyroid gland pathologies and coronary artery disease, whose surgical treatment may be performed simultaneously. In this case, we present a case of a patient with substernal thyroidectomy concurrent with off-pump coronary artery bypass grafting. A 57-year-old female patient was admitted to the hospital with exertional dyspnoea, intermittent coughing and stable angina pectoris. The substernal goitre measuring 5x5x4 cm was accompanied by a 95% in-stent restenosis at the left anterior descending artery. Thyroidectomy and off-pump coronary artery bypass grafting procedures were performed simultaneously. The postoperative period was uneventful and the patient was discharged 5 days after the operation. This case indicates that off-pump revascularisation seems to be a better option in cases where surgical interventions for thyroid and coronary artery diseases are necessary instead of on-pump revascularisation where the adverse effects of the cardiopulmonary bypass are considered.
Keywords: Substernal Thyroidectomy; Off-pump Coronary; Cardiopulmonary Bypass